Two new species of Staphylus (Scantilla) Godman and Salvin, 1896 (Lepidoptera, Hesperiidae, Pyrginae, Carcharodini) from Colombia and Mexico - Lemes, José Ricardo Assmann; Warren, Andrew David; Siewert, Ricardo Russo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2025)
Two new species of Staphylus (Scantilla) are described: Staphylus (Scantilla) bondus A. Warren, H. A. Freeman & Lemes, sp. nov. from Colombia, and Staphylus (Scantilla) freemani A. Warren & Lemes, sp. nov. from Mexico. The two new species can be identified by several wing and genitalia characters that differentiate them from other species in this subgenus. Female genitalia of this subgenus is illustrated for the first time. Analysis of COI data supports both taxa as new species and agrees with morphological characters in placing them in the subgenus Scantilla.